A Profile of Low Back Pain: Treatment and Costs Associated With Patients Referred to Orthopedic Specialists in Sweden. Issue 17 (1st September 2017) - Jonsson, Emma; Olafsson, Gylfi; Fritzell, Peter; Hägg, Olle; Borgström, Fredrik
Abstract : Study Design: Analysis of Swedish national and regional register data. Objectives: The aim of this study was to characterize healthcare resource utilization, productivity loss, and costs of patients with low back pain (LBP) with or without leg pain, who have been referred from primary care settings to orthopedic specialist care. Summary of Background Data: Register data on outpatient and inpatient care, work absence, drug prescriptions, socioeconomics, and mortality were extracted for patients visiting orthopedic specialists for LBP in the Swedish region Västra Götaland (1.6 million inhabitants in 2015) in 2008 to 2011 (4 years). Methods: Patients were followed with regard to resource use and costs during "LBP episodes, " defined as the time period from the first visit to an orthopedic specialist ("index-point") until the last observed resource use registered with an LBP diagnosis. Patients were also followed during fixed time periods of 2 years before and 2 years after the index-point. Results: In total, 16, 329 LBP episodes were identified (13, 931 unique patients), in six diagnosis groups. Mean societal cost per LBP episode was estimated at [Euro sign]6466 (SD 21, 884), where indirect cost constituted 74% and half of the 26% remaining direct costs were owing to hospital inpatient care. Patients underwent surgery in 10% of the episodes (n = 1583). Cost per LBP episode varied between diagnosis groups, with a range of [Euro sign]18, 668 to [Euro sign]40, 774 in episodes with surgery and [Euro sign]978 to [Euro sign]10, 379 in episodes without surgery. Assessment of the fixed time period of 2 years before and after index-point showed that costs increased gradually during the year before in all groups and declined the year after in all groups. Conclusion: The marked decline in total costs the year after referral to an orthopaedic specialist indicates that the treatment provided, regardless of treatment, has an effect and also likely improves the quality of life for the patient. Level of Evidence: 4